2019
DOI: 10.1016/j.jfma.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease and its treatment in 2018: Global and Taiwanese status updates

Abstract: The global incidence and prevalence of inflammatory bowel disease (IBD) has increased over the last 2-4 decades, likely because of the adoption of a more "western" lifestyle as well as improved detection and awareness, and Taiwan is no exception. To characterize the increasing burden of IBD, we conducted a comprehensive review of IBD in the existing literature. The following parameters were reviewed: background knowledge and current standard care for IBD, including natural history, epidemiology, pathogenesis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 84 publications
0
45
0
14
Order By: Relevance
“…However, clinicians should be advised to change their treatment strategy for patients with CD; 5-ASA only exhibits a marginal effect on CD, and our results indicated that incidence of intraabdominal abscess increased when disease activity was not fully under control. A relatively low number of cases with therapy escalation were identified among the UC patients because of concerns regarding the adverse effects of immunosuppressants and because the NHI began reimbursing patients for anti-TNF-α agents in September 2016 [ 41 ]. The “treat to target” idea appeared to have been implemented during the present study period; we identified relatively high numbers of patients who had received immunomodulators and biologics.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinicians should be advised to change their treatment strategy for patients with CD; 5-ASA only exhibits a marginal effect on CD, and our results indicated that incidence of intraabdominal abscess increased when disease activity was not fully under control. A relatively low number of cases with therapy escalation were identified among the UC patients because of concerns regarding the adverse effects of immunosuppressants and because the NHI began reimbursing patients for anti-TNF-α agents in September 2016 [ 41 ]. The “treat to target” idea appeared to have been implemented during the present study period; we identified relatively high numbers of patients who had received immunomodulators and biologics.…”
Section: Discussionmentioning
confidence: 99%
“…IBD is a catastrophic illness in Taiwan and proof of diagnoses has to be reviewed by special committee. The diagnosis of IBD was based on medical history, clinical evaluation, endoscopic findings, and histological findings [ 24 , 25 ]. Censoring was defined as death, the date of diagnosis of IBD, or the end of the follow-up period on 31 December 2013.…”
Section: Methodsmentioning
confidence: 99%
“…Inflammatory bowel disease (IBD) has two main forms, including Crohn's disease (CD) and ulcerative colitis (UC). UC is a chronic relapsing disease of the colon and rectum characterized by inflammation and ulceration of the mucosa (Su et al, ). Bloody mucoid stool, diarrhea, and rectal urgency are common gastrointestinal manifestations of UC.…”
Section: Introductionmentioning
confidence: 99%